Challenges and strategies for reducing pesticide use from the perspecitve of civil society organizations in Chiapas, Mexico - Anaya Zamora, Ixchel Carolina; Mier y Terán Giménez Cacho, Mateo; Urdapilleta Carrasco, Jorge; Ferguson, Bruce (Agricultura, Sociedad y Desarrollo, 2020)
In order to reduce and even eliminate pesticide use and build sustainable agri-food systems, there is a need to take into account economic, political, and cultural factors, as well as actors involved. This study explores strategies and challenges to reducing or eliminating pesticide use, faced by Civil Society Organizations (CSOs) of Chiapas whose work is related to agri-food systems. Using a qualitative method based on semi-structured interviews and narrative analysis, we defined four categories of CSOs with respect to their position on pesticides: a) indiscriminate use, b) regulated use, c) transition, and d) no use. We identified the main strategies and challenges of such CSOs in reducing and even eliminating pesticide use. Their strategies include respecting autonomy in order to maintain communication channels; sharing information; consciousness raising involving CSOs and farmers; developing and strengthening alternative spaces such as markets, seed fairs, and demonstration plots; networking; and defining a political position advocating agroecology.